Possible mechanisms limiting movement of Ralstonia solanacearum in resistant tomato tissues - Nakaho, K.; Hibino, H.; Miyagawa, H. (Wiley, 2000)
The distribution and appearance of Ralstonia solanacearum in the upper hypocotyl tissues of root‐inoculated tomato seedlings of resistant rootstock cultivar LS‐89 (a selection from Hawaii 7998) and susceptible cultivar Ponderosa were compared to clarify the mechanism that limits the movement of the bacterial pathogen in resistant tomato tissues. In stems of wilted Ponderosa plants, bacteria colonized both the primary and the secondary xylem tissues. Bacteria were abundant in vessels, of which the pit membranes were often degenerated. All parenchyma cells adjacent to vessels with bacteria were necrotic and some of them were colonized with bacteria. In stems of LS‐89 plants showing no discernible wilting symptoms, bacteria were observed in the primary xylem tissues but not in the secondary xylem tissues. Necrosis of parenchyma cells adjacent to vessels with bacteria was observed occasionally. The pit membranes were often thicker with high electron density. The inner electron‐dense layer of cell wall of parenchyma cells and vessels was thicker and more conspicuous in xylem tissues of infected LS‐89 than in xylem of infected Ponderosa or mock‐inoculated plants. Electron‐dense materials accumulated in or around pit cavities in parenchyma cells next to vessels with bacteria, and in vessels with bacteria. Many bacterial cells appeared normal in vessels, except for those in contact with the pit membranes. These results indicate that R. solanacearum moves from vessel to vessel in infected tissues through degenerated pit membranes and that restricted movement in xylem tissues was the characteristic feature in LS‐89. The limitation in bacterial movement may be related to the thickening of the pit membranes and/or the accumulations of electron‐dense materials in vessels and parenchyma cells.